Dual-faced circRNAs: orchestrating immunosuppression and activation in the lung cancer microenvironment - Li, Junyao; Zhang, Lin; Wang, Yicun; Li, Chunyan (Frontiers in Cell and Developmental Biology, 2025)
Circular RNAs (circRNAs), a class of non-coding RNAs characterized by covalently closed-loop structures, have emerged as key regulators in the tumor immune microenvironment (TIME) of lung cancer, owing to their high stability, tissue-specific expression, and multidimensional regulatory capabilities. This review systematically synthesizes the latest research progress and elucidates the processes by which circRNAs regulate the functional states of immune cells in the TIME through diverse molecular mechanisms, including acting as competing endogenous RNAs (ceRNAs) to sequester microRNAs (miRNAs), interacting with RNA-binding proteins (RBPs), and in some cases, encoding functional polypeptides. CircRNAs possess bidirectional regulatory capacities: they can promote tumor immune evasion by modulating the expression of immune checkpoint molecules, influencing the infiltration and activity of effector immune cells (e.g., CD8+ T cells), recruiting immunosuppressive cells (e.g., regulatory T cells and M2-type macrophages), and regulating immune signaling pathways; meanwhile, they can also activate antitumor immune responses. Furthermore, the review explores the potential of circRNAs as liquid biopsy biomarkers for lung cancer diagnosis and prognosis, as well as their translational prospects in therapeutic strategies including vaccines, circRNA-enhanced CAR-T therapy, and formulations encoding immunomodulatory factors. Despite challenges such as complex mechanisms, low delivery efficiency, and safety concerns, the development of multi-omics technologies, novel delivery systems, and gene-editing tools provides directions for the development of precision therapies targeting circRNAs, which aim to reshape the lung cancer immune microenvironment and overcome immunotherapy resistance.